KASDIENYBĖ KAIP KLA SIKINĖS FILOSOFIJOS PARAŠTINIS FENOMENAS. - Milerius, Nerijus (Problems / Problemos, 2018)
The article deals with the relationship between philosophy and the everyday in the classical paradigm. The separation between philosophy and the everyday, embedded in the story of Thales and a servant, is transposed into the discourse of ontology and gnoseology. Plato's cave allegory is interpreted as ontological, and Descartes's theory as gnoseological way of transcendence and elimination of the everyday life. The article argues that under the domination of classical paradigm the everyday is treated as an obstacle to the achievement of philosophical knowledge. That is why contemporary philosophy, which rehabilitates the everyday, seeks to diversify the unified concept of everyday life and to show that everyday life is a multi-faceted entity in which different powers of the everyday can coexist.